(untitled) (Journal of Event, Tourism and Hospitality Studies, 2022)
The driving role of technology in building a sustainable and resilient future has been long acknowledged. As one of the most resilient industries, the hospitality sector is the focus of this research, particularlythe hotel lodging industry in the Bucharest metropolitan area (Romania’s capital city) as it relates to passenger traffic at two important international transportation hubs: the international airport and railway station. The site selection, or selection of an appropriate location for lodging, is astrategic choice. The distinction between success and failure is also determined by other external factors as well as internal company factors. There is a wealth of literature on business location, and the main approaches are highlighted in the section onliterature reviews. Future research will need to address the issue of business location in relation to transportation hubs that can attract potential customers. There are two specific questions to reach the research objective: to find out if the traffic from the transit terminals influences the number of accommodation facilities and if there is a specific pattern for choosing the location of tourist accommodation facilities (hotels) in the studied area. The investigation methodology consists of both secondary sources and primary research, respectively: national statistics as well as international databases such as Google Maps and OpenStreetMap, extensively use the geographic information system (GIS) database and software tools (QGIS 3.22 and Google Earth Pro 7.3.4.8573). The intent is to find whether there is a relationship between the two databases studied. It can be concluded that the number of tourist accommodation facilities and its locations are related to the main passenger traffic flows from/to the Bucharest “Henry Coanda” International Airport OTP and Bucharest North Railway station. The results, which are presented in both tabular and dynamic graphical formats, are beneficial for scholars and mostly for practitioners and businesspeople. Besides, the findings from this study is valuable for policymakers and strategists at a macroeconomic level, as well as for tourism and hospitality entrepreneurs and managers. The implications are highlighted, and recommendations are presented in this paper.